2020
DOI: 10.3390/agronomy10030426
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Recent Climate Change on Potato Yields at a Provincial Scale in Northwest China

Abstract: Understanding the effects of climate change on potato yield is vital for food security in northwest China. Based on the long-term data of yields and meteorology, this study analysed the impacts of recent climate change on potato yields at a provincial scale in northwest China. The first difference method was used to disentangle the contributions of climate change from the changes in potato yield in two consecutive years. The moving average method was used to decouple the climate-induced yield of potato. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…This study also found that, in every crop year, potato cultivated areas increased in Bangladesh [42,54]. Similar findings were also observed by Li and Zhang, who found that climatic factors variously affect different potato producing provinces in China [55]. The elasticity of the lagged year's farm price was 0.04-0.12, indicating that potato prices played a significant role in deciding the allocation of lands and that they had a positive and statistically associated effect on potato producer behavior.…”
Section: Estimation Of Functions Of the Supply And Demand Modelsupporting
confidence: 85%
See 1 more Smart Citation
“…This study also found that, in every crop year, potato cultivated areas increased in Bangladesh [42,54]. Similar findings were also observed by Li and Zhang, who found that climatic factors variously affect different potato producing provinces in China [55]. The elasticity of the lagged year's farm price was 0.04-0.12, indicating that potato prices played a significant role in deciding the allocation of lands and that they had a positive and statistically associated effect on potato producer behavior.…”
Section: Estimation Of Functions Of the Supply And Demand Modelsupporting
confidence: 85%
“…The continuing effects of climate change on potato production are assumed to become more complicated and uncertain. Due to data availability, this study did not assess fertilizer effects, CO 2 concentrations, and severe climatic events that negatively affect potato yields [55,77,78]. Further detailed and comprehensive assessments are needed for future studies along with assessment of the development of crop cultivars and producers' behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In northern China, the potato yield was most susceptible to changes in the diurnal temperature range, followed by radiation, precipitation, and evapotranspiration [ 17 ], late potato development was sensitive to the optimum temperature setting in northern Europe [ 18 ], and spatial variability impacts potato production [ 19 ]. The maximum temperature, comparatively heavy rain, and irrigation all had an effect on the yield of potatoes in China [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…By increasing temperature in stolons and roots is caused to promote early senesce of plants (Menzel, 1983;Menzel, 1985;Struik et al, 1989;Prange et al, 1990;Lafta and Lorenzen, 1995). Li and Zhang (2020) proved that potato yield was decreased by 583 kg ha -1 for every increment of temperature by 1  C in china. According to Dam et al (1996), tuber formation is delayed under higher temperatures on long days.…”
Section: Effect Of Temperature On Tuber Formationmentioning
confidence: 99%
“…Wang et al (2013) observed that mulch with trickle irrigation is secured more tubers under water deficit conditions. Li and Zhang (2020) revealed that potato yield was increased with every 100 mm increasing of precipitation in the rainfed area of China. According to Jama-Rodzenska et al (2020), stolons' weights were higher in cv.…”
Section: Effect Of Drought and Irrigation On Tuber Formationmentioning
confidence: 99%